Usefulness of serum opsonic activity measured by chemiluminescence method to assess the invasiveness of colorectal endoscopic mucosal dissection. (1st December 2020) - Chinda, Daisuke; Shimoyama, Tadashi; Arai, Tetsu; Sawada, Kaori; Akitaya, Kazuki; Kudo, Sae; Yasuda, Kohei; Miyazawa, Kuniaki; Akimoto, Naoki; Sato, Satoshi; Hayamizu, Shiro; Tatsuta, Tetsuya; et al.
Abstract: Endoscopic sub-mucosal dissection (ESD) is considered as a low-invasive treatment for early-stage colorectal cancer, but the degree of invasiveness has not been well investigated. The aim of this study was to evaluate the physical stress due to colorectal ESD based on changes in serum opsonic activity (SOA). SOA was examined by measuring reactive oxygen species (ROS) produced by neutrophils using lucigenin-dependent chemiluminescence (LgCL) and luminol-dependent chemiluminescence (LmCL). Sixty-nine patients were enrolled into the study and examined SOA in the morning of the day of ESD, the next day, and at four days after ESD. The peak height (PH) and area under the curve (AUC) of LgCL showed no significant difference between the day and the next day, whereas the PH and AUC for LgCL were significantly higher four days after ESD than on the day of ESD ( p  < .05). In contrast, the PH and AUC of LmCL showed no significant changes during the ESD perioperative period. This difference suggests that SOA changes during the colorectal ESD perioperative period involved minor increases in the production of lower-toxicity ROS. This finding supports the position that ESD is a technique that does not generate a great deal of physical stress. On the other hand, a significant increase in SOA at four days after colorectal ESD suggests that care is needed with postoperative management even after the patient has started to eat meals again.